Pengembangan Panduan Bibliokonseling untuk Meningkatkan Self Esteem pada Peserta Didik SMA di Karanganyar - Kevin Setiawan; Agus Tri Susilo; Citra Tectona Suryawati (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: This research and development aim to produce products that meet the relevance criteria, namely the development of bibliocounseling guidelines to increase self-esteem in high school students in Karanganyar. Based on the results of empirical and theoretical studies ready to meet the criteria of consistency, efficiency, and effectiveness. This research uses research and development methods according to Plomp & Nieveen, which are divided into three stages; preliminary research, development phase (prototyping), and assessment phase. Product development is based on preliminary investigation analysis through questionnaires and interviews. This research and development have only reached the second stage, namely the development or prototyping phase, which has been carried out to produce a product, namely guidelines and worksheets for counseling and counseling to increase self-esteem in high school students in Karanganyar. The resulting bibliocounseling guidelines meet the relevance criteria. Relevance criteria were obtained through empirical studies and theoretical studies. The product in this study still needs to meet the criteria for consistency, practicality, and effectiveness to reach the research and development phase of the assessment phase. This manual consists of two books, namely (1) manuals and (2) worksheets. Suggestions for further researchers to be able to proceed to the next stage, namely the assessment phase, and examine the acceptability of this product in the broader scope of the school. Abstrak: Penelitian dan pengembangan ini bertujuan untuk menghasilkan produk yang memenuhi kriteria relevansi, yaitu pengembangan pedoman bibliocounseling untuk meningkatkan harga diri (self esteem) pada peserta didik SMA di Karanganyar. Berdasarkan hasil studi empiris dan studi teoretis siap memenuhi kriteria konsistensi, efisiensi dan efektivitas. Penelitian ini menggunakan metode penelitian dan pengembangan menurut Plomp & Nieveen, yang terbagi menjadi 3 tahap; penelitian pendahuluan, fase pengembangan (pembuatan prototipe), fase penilaian. Pengembangan produk berdasarkan analisis investigasi pendahuluan melalui kuesioner dan wawancara. Penelitian dan pengembangan ini baru sampai pada tahap kedua yaitu development or prototyping phase, yang telah dilakukan hingga menghasilkan produk yaitu panduan dan lembar kerja bibiliokonseling untuk meningkatkan self esteem pada peserta didik SMA di Karanganyar. Pedoman bibliocounseling yang dihasilkan memenuhi kriteria relevansi. Kriteria relevansi diperoleh melalui kajian empirik dan kajian teoritik. Produk dalam penelitian ini masih perlu memenuhi kriteria consistency, practically dan effectiveness. agar dapat sampai pada tahap penelitian dan pengembangan assessment phase.  Panduan ini terdiri dari dua buku, yaitu (1) buku panduan dan (2) lembar kerja. Saran bagi peneliti selanjutnya untuk dapat melanjutkan pada tahap berikutnya yaitu assessment phase serta mengkaji keberterimaan produk ini di ruang lingkup sekolah yang lebih luas.